2020
DOI: 10.7861/fhj.2019-0034
|View full text |Cite
|
Sign up to set email alerts
|

Exploring communities of practice in the NHS: A core medical trainee experience

Abstract: Objectives A community of practice was described by Lave and Wenger as a mutual engagement using a shared repertoire of resources to attain a shared goal. This study explored the extent to which NHS workplaces function as communities of practice for core medical trainees. Methods All core medical trainees in one region were invited to a semi-structured interview. A framework was produced using communities of practice themes and a hybrid deductiveinductive method used for data analysis. Results NHS workplaces f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Locum contracts can be ended early following even low-level concerns and locums may have less access to communities of practice within Trusts for providing appropriate governance, leadership and support, meaning remedying performance problems may be more difficult. Similarly, Amery and Griffin (2020) found that short training rotas limited the ability of medical trainees to engage in communities of practice in order to engage in activities and form mutual relationships [ 35 ]. This may in part explain why locums are more likely to have formal complaints about them to the professional regulator than permanent doctors [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Locum contracts can be ended early following even low-level concerns and locums may have less access to communities of practice within Trusts for providing appropriate governance, leadership and support, meaning remedying performance problems may be more difficult. Similarly, Amery and Griffin (2020) found that short training rotas limited the ability of medical trainees to engage in communities of practice in order to engage in activities and form mutual relationships [ 35 ]. This may in part explain why locums are more likely to have formal complaints about them to the professional regulator than permanent doctors [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Published evidence also describes a similar role of CoP in healthcare institutions where CoP are frequently encourage collaborative culture and knowledge utilization. Organizations like the National Health Services (NHS) of UK recommend that for a sustainable change within an organization, it is vital to link the process of change with active CoP 11 . Informal CoP functions as morning meetings to discuss difficult clinical cases or academic challenges.…”
Section: Discussionmentioning
confidence: 99%
“…A ‘community of practice’ is a powerful concept in learning. It describes a group of people ‘who share a common concern or a passion for something they do and learn how to do better as they interact regularly.’ 19 Communities of practice within the field of echocardiography are crucial because they facilitate learning from the moment a novice enters the echo room for the first time. Communities of practice powerfully signal the legitimacy of the individual participant, however inexperienced they are, whether that is within an actual practice environment or within a wider concept of a community, for example through the BSE.…”
Section: Solutions: a 10-year Roadmapmentioning
confidence: 99%